Innovative Learning Strategies and Methods to Overcome Difficulties in Reading the Qur'an - Muh. Alif Kurniawan; Zalik Nuryana; Anaas Tri Ridlo Dina Yuliana; Arif Rahman (Al-Misbah (Jurnal Islamic Studies), 2021)
Ideally, for junior high school, students can read the Qur'an even though the reading is still haltingly. However, reading the Qur'an is one of the severe problems faced by junior high schools that exist today. One of them is at SMP Muhammadiyah 1 Kalasan. Most of the students have not been able to read the Qur'an, even though SMP Muhammadiyah 1 Kalasan is one of the schools that is integrated with the Tahfidz PCM Kalasan House. As the landscape spearhead, teachers must have various strategies and methods to overcome these problems. So that the main program of the school to become a school that prints hafidz Al-Qur'an can be realized as well as possible. A good strategy and method will support the success of overcoming difficulties in reading the Qur'an. The purpose of this study was to find out strategies and innovative learning methods to overcome difficulties in reading the Qur'an at SMP Muhammadiyah 1 Kalasan. This study uses a qualitative research method using a descriptive approach. The data in this study using interviews, observation, and documentation. The results of this study are related to innovative learning strategies and methods to overcome difficulties in reading the Qur'an, including drill method/spelling practice, peer tutoring method, active learning strategy, and one-day one-page iqro' strategy. These strategies and methods are used step by step, starting from the initial to the final stage with a link system.